Separation of electroencephalogram low-frequency components on the basis of the stochastic resonance effect - Kharchenko, O.I.; Lonin, Yu.F.; Zabrodina, L.P.; Kartashov, V.M. (Вопросы атомной науки и техники, 2021)
The paper describes the method for electroencephalogram (EEG) analysis based on the stochastic resonance (SR) effect. The numerical computation has provided the separation of low frequency components that fall within the δ-rhythm band. This is currently central in the neuropathology diagnostics, because the presence of low frequencies in the EEG is abnormal and bears witness to the disease. For verification, the data obtained with the use of the SR effect have been compared with the computations based on the autocorrelation function (ACF) processing. The comparison has shown their good agreement. Наведено метод аналізу електроенцефалограм (ЕЕГ) на основі ефекту стохастичного резонансу. Чисельний розрахунок дозволив виділити низькочастотні складові, які потрапляють у смугу δ-ритму, що є актуальним у діагностиці нервових хвороб, оскільки низькі частоти в ЕЕГ є патологічними і свідчать про захворювання. Для верифікації отриманих результатів було проведено порівняльний аналіз численних розрахунків на основі ефекту стохастичного резонансу та розрахунків на основі автокореляційної функції, який показав їх гарний збіг. Приведен метод анализа электроэнцефалограмм (ЭЭГ) на основе эффекта стохастического резонанса. Численный расчет позволил выделить низкочастотные составляющие, которые попадают в полосу δ-ритма, что является актуальным в диагностике нервных болезней, поскольку низкие частоты в ЭЭГ являются патологичными и свидетельствуют о заболевании. Для верификации полученных результатов был проведен сравнительный анализ численных расчетов на основе эффекта стохастического резонанса и расчетов на основе автокорреляционной функции, который показал их хорошее совпадение.